Perceived Health Locus of Control, Self-Esteem, and Its Relations to Psychological Well-Being Status in Iranian Students - Moshki, M (Tehran University of Medical Sciences, 2010)
BACKGROUND: Health locus of control (HLC) has been associated with a variety of ailments and health outcomes and designed to predict behaviors and cognitive processes relevant to mental and physical health. This study investigated the relationships between perceived health locus of control, self-esteem, and mental health status among Iranian students. METHODS: In this analytical study the subjects were recruited from students in Gonabad University of Medical Sciences, Iran, who studied in the first year (N=154). Students completed the questionnaires for assessing demographic, perceived health locus of control, self - esteem and psychological well- being data. RESULTS: The statistical analysis revealed a negative relationship between perceived Internal HLC and self-esteem with psychological well-being. The positive correlation of the perceived Chance HLC with psychological well-being was statistically significant (r= 0.21, P< 0.01) and the positive correlation of the perceived Internal HLC with self-esteem was statistically significant (r= 0.25, P< 0.01). A significantly direct relationship between low perceived Internal HLC, self–esteem and psychological problems was found among these students. CONCLUSION: The findings will be addressed in relation to their implications for effective mental health education based on health locus of control especially internal and powerful others beliefs associated with self-esteem for students. This will require additional monitoring and uninterrupted trying in order to be effective.